EVALUASI PROSEDUR PENGERITINGAN VERTIKAL DAN KENDALA PELAKSANAANNYA DI SALON TUPADEAR - Kezya Lauren br Siagian; Intan Salsa Annisa; Lentina Pardede; Laila Hafizah Rangkuti; Asrah Rezki Fauzani; Mutia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of vertical hair perming procedures and to identify the obstacles encountered in practice at Tupadear Salon. This research uses a descriptive qualitative approach with data collection techniques through interviews and direct observation. The subject of the study is a professional salon assistant who has experience in performing vertical hair perming. The results show that the vertical perming procedure consists of several stages, including hair condition analysis, preparation, sectioning, vertical rolling, chemical application, two-stage drying process, neutralization, and finishing. The drying process takes approximately 60–90 minutes. The success of the perm is highly influenced by hair condition, where virgin hair produces more optimal curls compared to chemically treated hair such as smoothed or colored hair. The vertical perming technique has advantages in terms of faster working time and more natural-looking curls. However, the main obstacle found is damaged or unhealthy hair, which leads to less optimal results. Therefore, proper hair analysis and post-perming treatment are essential factors in achieving successful outcomes.